Settlement and load transfer mechanism of a pile group adjacent to a deep excavation in soft clay. (April 2018) - Shakeel, M.; Ng, Charles W.W.
Abstract: Three-dimensional coupled consolidation analysis is conducted to gain insight into the response of a 2 × 2 floating pile group adjacent to deep excavation in soft clay. By using a validated finite element model, the influence of the excavation depth, pile length, pile group location from excavation, the supporting system stiffness, soil state and permeability, and working load are systematically studied. The analysis revealed that the maximum settlement occurs when the pile group is founded at the excavation level and at a distance of 0.75-times the excavation depth, although the induced bending moment is minimum. In contrast to pile group settlement, tilting is maximum when it gets closer to the wall and minimum at a distance of 0.75-times the excavation depth. It is also observed that the influence of system stiffness is more pronounced for the flexible wall and when the pile group is located at the excavation level. Applied working load influences pile group settlement but has relatively minor effects on pile group tilting. Excess negative pore water pressures are generated in the soil elements due to excavation. Pile group experiences progressive long term settlement with the dissipation of excess negative pore water pressure.